Zeolites and Catalysis 2010
DOI: 10.1002/9783527630295.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Chemistry of Zeolite Reactivity

Abstract: IntroductionNowadays, advances in chemical theory rely to a significant extent on computations. Novel theoretical concepts arising directly from experiments usually require further investigations using computational modeling. This is necessary to develop a conclusive molecular-level picture of the observed phenomenon. As a result, computational methods are nowadays widely and extensively applied in the chemical, physical, biomedical, and engineering sciences. They are used in assisting the interpretation of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…The vdW interaction between these subunits represents the vdW stabilization of the confined hydrocarbon species. Previous studies have shown that the addition of the empirical corrections to the results obtained at the PBE level results in both thermodynamic and kinetic parameters that are very close to those obtained at the higher ab initio level [88]. a-and b-sites represent a six-membered ring (6MR) in the straight channel and a deformed 6MR at the intersection of straight and sinusoidal channels, respectively [89].…”
Section: Computational Detailsmentioning
confidence: 67%
“…The vdW interaction between these subunits represents the vdW stabilization of the confined hydrocarbon species. Previous studies have shown that the addition of the empirical corrections to the results obtained at the PBE level results in both thermodynamic and kinetic parameters that are very close to those obtained at the higher ab initio level [88]. a-and b-sites represent a six-membered ring (6MR) in the straight channel and a deformed 6MR at the intersection of straight and sinusoidal channels, respectively [89].…”
Section: Computational Detailsmentioning
confidence: 67%
“…This could result in possible confinement effects. Pidko and van Santen [65] have emphasized that in low-silica zeolites, where the density of exchangeable cations is high, the intrazeolite arrangement of cations plays a crucial role in activity and selectivity since these ions can undergo multiple noncovalent interactions with the reactants, resembling the active sites encountered in enzymes. Such interactions are present even with small molecules such as N 2 O 4 [66].…”
Section: Page 12 Of 39mentioning
confidence: 99%
“…Modern computational methodologies provide practical tools to address the structural problem of zeolite catalysis at the molecular level. 231 , 232 Quantum chemical calculations, including semi-empirical methods, ab initio methods, and density functional theory (DFT), have made significant contributions to elucidate the molecular nature of active sites in zeolite catalysts. DFT calculations are currently considered as the most efficient methods due to a good balance between computational speed and accuracy.…”
Section: Advanced Characterization Methods In Single-site Zeolite Catmentioning
confidence: 99%
“…The conventional preparation methods of zeolite-based transition metal catalysts usually give a variety of different intrazeolite species, which makes it very challenging to unambiguously identify the active sites solely by experiential characterization techniques. Modern computational methodologies provide practical tools to address the structural problem of zeolite catalysis at the molecular level. , Quantum chemical calculations, including semi-empirical methods, ab initio methods, and density functional theory (DFT), have made significant contributions to elucidate the molecular nature of active sites in zeolite catalysts. DFT calculations are currently considered as the most efficient methods due to a good balance between computational speed and accuracy.…”
Section: Advanced Characterization Methods In Single-site Zeolite Cat...mentioning
confidence: 99%